ENSAIO SOBRE O COTIDIANO: DE MARÍLIA GARCIA A YASUJIRO OZU - Arantes, Júlia Carolina (Inventário, 2025)
This essay aims to investigate artistic works, such as the literature of Marília Garcia and Virginia Woolf and the films of Yasujiro Ozu, Jim Jarmusch, and Hou Hsiao-hsien, which focus on the banality of the existence in order to theorize the everyday life. These works depict the infraordinary, as Georges Perec calls the small life that is not reported or advertised, as an attempt to revalue the subtlety and delicacy of everyday experiences that have become invisible. This essay also investigates the collection and the repetition as a way to prevent the oblivion of subtle events that, despite recurring daily, can be ignored and go unnoticed. Based on the theoretical works of Georges Didi-Huberman, Denilson Lopes, and Peter Pál Pelbart, and in contrast to the monumentality of the great history, this essay is interested in how the anonymous lives of ordinary men, with their average stories, neither epic nor tragic, are portrayed in literature and cinema.